Dragon was terrible - DiPucchio, Kelly; Pizzoli, Greg (New York : Farrar Straus Giroux, 2016)
When a dragon has a temper tantrum, no one can tame him, except for a little boy with a good book.
Keywords: Dragons -- Fiction; Temper tantrums -- Fiction; Behavior -- Fiction; Books and reading -- Fiction